MOTIVASI AUSTRALIA MENERAPKAN KEBIJAKAN SEKURITISASI TERHADAP IRREGULLAR MARITIME ARRIVALS (IMA) TAHUN 2001-2008 - Tanzila, Elya; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explain about Austrlia’s motive implemented securitization policy toward Irregullar Maritime Arrivals. For many years, the number of Irregullar Maritime Arrivals have been increased in Australia. This research is aimed to explain the reasons of Australia implemented those policies to against Irregullar Maritime Arrivals which known as Pacific Solution. This reasearch theoretically has built with neo-realism perspective on International Relations and supported by securitization theories, and also the concept of non-traditional security. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is Australia policy towards Irregullar maritime Arrivals in the year of 2001 until 2008. This result shows that the reasons of Australia implementated Pacific Solution are Australia worried about people smuggling, the issue of Islamophobia , and various acts of criminality arising from Irregullar Maritime Arrivals. Keywords : Irregullar Maritime Arrivals Securitization, non-traditional security, people smuggling, Islamophobia, Pacific Solution.